(untitled) (Journal of the College of Basic Education, 2022)
Thirty nine bacterial species were identified among forty one samples that were collected from patients suffering from otitis media. These species were Pseudomonas aeruginosa, Staphyllococcus aureus, Proteus mirabilis, Klebsiella pneumonia and E. coli. Antibiotic sensitivity test was performed to these isolates. Then the antibacterial activity of two plant aqueous extracts was performed. The extracts were from Solanum nigrum (black nightshade) and Allium cepa (onion). Both extracts affect negatively on the growth of selected bacterial isolates but at different levels and at different concentrations. The aqueous extract of black night shade predominate at onion extract especially at concentration 1000mg/ml at P<0.05. S. aureus was the most affected bacteria especially with black nightshade while P. mirabilis was the least. Klebsiella pneumonia, P. aeruginosa and E.coli came as second , third and fourth respectively according to their sensitivity to black nightshade extract.